Hubungan Dukungan Sosial Dan Kencenderungan Kepribadian Ekstrovert Dengan Kesejahteraan Psikologis Pada Siswa SMA Negeri 1 Binjai - Siti Fuji Sugesty; Sri Mifayetty; Hasanuddin Hasanuddin (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2021)
The correlation between social support and extrovert personality tendencies and psychological well-being were examined in a sample of 369 students at SMA Negeri 1 Binjai, North Sumatra. The research was conducted from Oktober 2019 to April 2020. The proposed hypothesis; there was a correlation between social support and extrovert personality tendencies with psychological well-being among students. Data were collected through a scale of psychological well-being, social support scale, and extrovert personality tendency scale.  Using multiple regression analysis we found that the coefficient Freg = 346,958; sig 0.010, then the three hypotheses proposed in this study were accepted. The two variables in this study, namely the variable social support and extrovert personality tendencies, contributed 65.5% to psychological well-being. Separately, social support and  the extrovert personality tendency  contributed 65.4% and 60.4% respectivelly to the level of psychological well-being. We concluded that Social support, extrovert personality tendencies (the correlation coefficient rx1y = 0.809; sig 0.010, and  rx2y = 0.777; sig 0) had  a significant relationshi correlation to psychological well-being as well as both  social support and extrovert personality simultaneously